(NiSTORIQ ZARUBEVNOJ LITERATURY (BXVIII (NWEKA (B:s (Nu^EBNOE POSOBIE (B/s - (NsAMARIN(B, (Nr(B.(Nm(B.s; (NnEUSTROEW(B, (Nw(B.(Np(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1974)
(NsPISOK LIT(B.: (NS(B. 402-405. (NiMEN UKAZ(B.: (NS(B. 406-412s
Keywords: (NlITERATURA ZARUBEVNYH STRAN(B, 18 (NW(B.s